Development And Characterization Of Polypropylene-Based Antimicrobial Active Packaging Incorporated With Transcinnamaldehyde - Lim, Qai Yeing (Universiti Sains Malaysia, 2021)
Antimicrobial active packaging provides an ideal solution for food industry to preserve the quality and safety of reduced additives and minimally processed food. In this study, antimicrobial active film packaging was produced by incorporating 5% w/w transcinnamaldehyde (CIN) in the polypropylene (PP) polymer matrix using twin-screw extrusion and blow film extrusion